The VHL protein recruits a novel KRAB-A domain protein to repress HIF-1α transcriptional activity - Li, Zaibo (Oxford University Press, 2003)
The von Hippel-Lindau tumor suppressor (pVHL) is a component of an E3 ubiquitin ligase and targets hypoxia-inducible factor-1α (HIF-1α) for ubiquitylation and degradation under normoxic conditions. pVHL also directly inhibits HIF-1α transactivation by recruiting histone deacetylases. Here, we report a novel pVHL-interacting protein that functions as a negative regulator of HIF-1α transactivation. This protein, generated from the ZnF197 locus by alternative splicing, contains a Kruppel-associated box (KRAB)-A domain and a SCAN domain, but lacks the 22 C2H2-type zinc fingers present in ZnF197. Therefore, we named this protein pVHL-associated KRAB-A domain-containing protein (VHLaK). We demonstrate that the KRAB-A domain in VHLaK mediates pVHL binding and functions as a transcriptional repression module. The SCAN domain mediates VHLaK homo-oligomerization, which enhances VHLaK repressive activity. pVHL can recruit VHLaK to repress HIF-1α transcriptional activity and HIF-1α-induced VEGF expression. Finally, we demonstrate that pVHL, VHLaK and KAP1/TIF-1β can be recruited into a single complex, indicating that KAP1/TIF-1β may participate in pVHL-mediated transcriptional repression of HIF-1α. Our findings provide a novel mechanism for the modulation of HIF-1α transactivation by pVHL.